Comparison of neurotoxicity of different aggregated forms of Aβ40, Aβ42 and Aβ43 in cell cultures. (16th February 2017) - Fu, Lu; Sun, Yao; Guo, Yongqing; Chen, Yan; Yu, Bin; Zhang, Haihong; Wu, Jiaxin; Yu, Xianghui; Kong, Wei; Wu, Hui
Abstract : The abnormal deposition of amyloid‐ β (A β ) peptides in the brain is the main neuropathological hallmark of Alzheimer's disease (AD). Amyloid deposits are formed by a heterogeneous mixture of A β peptides, among which the most studied are A β 40 and A β 42. A β 40 is abundantly produced in the human brain, but the level of A β 42 is remarkably increased in the brain of AD patients. Aside from A β 40 and A β 42, recent data have raised the possibility that A β 43 peptides may be instrumental in AD pathogenesis. Besides its length, whether the A β aggregated form accounts for the neurotoxicity is also particularly controversial. A β fibrils are generally considered as key pathogenic substances in AD pathogenesis. Nevertheless, recent data implicated soluble A β oligomers as the main cause of synaptic dysfunction and memory loss in AD. To further address this uncertainty, we analyzed the neurotoxicity of different A β species and A β forms at the cellular level. The results showed that A β 42 could form oligomers significantly faster than A β 40 and A β 43 and A β 42 oligomers showed the greatest level of neurotoxicity. Regardless of the length of A β peptides, A β oligomers induced significantly higher cytotoxicity compared with the other two A β forms. Surprisingly, the neurotoxicity of fibrils in PC12 cells was only marginally but not significantly stronger than monomers, contrary to previous reports. Altogether, our findings demonstrate the high pathogenicity of A β 42 among the three A β species and support the idea that A β 42 oligomers contribute to the pathological events leading to neurodegeneration in AD. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Neurotoxicity detection of different A β species (A β 40, A β 42 and A β 43 peptides) and different A β forms (monomers, oligomers and fibrils) at the cellular level. A β 42 exhibited the strongest ability to form oligomers or fibrils among the three A β species, and A β 42 oligomers induced a remarkably higher cytotoxicity compared with the other two A β forms.